Damaged and Defect Inventory Management System using Mobile Application - Suresh Gopal Krishnan,; Mohd Zainuri Saringat, (Applied Information Technology And Computer Science, 2022)
Any retail outlets typically consist of various products sold the company to consumers. Retail outlets that are popular typically consists of various branches in different locations that sells the same products as its other outlets. Despite having multiple branches, the products sold at each branch typically comes from a single central warehouse that stores all the products sold in big batches. This warehouse usually receives shipments from various factory and suppliers both locally andomestic. Due to the warehouse receiving various huge batches of products shipments, it is common to expects that not all the products receive will arrive in good condition. In such cases, the workers in the warehouse are required to make a statement on the damaged or defects product to later be used by the management. The method implemented to record and store such statements are currently done manually using paper and filling. As such, this method is proving to be outdated and not up to modern standard. The purpose of this project is to develop an android application that can assist in recording and storing such reports easily from the staff smartphones. With the completion of the application, it is hoped that the overall process and workflow involving recording and storing such reports will be improved positively.